Studi Evaluasi Analisa Kebutuhan Lahan Parkir Pasar Tradisional (Studi Kasus: Pasar Desa Sugio) - Firmansyah, Abdul Harist; Hartantyo, Sugeng Dwi (Jurnal Talenta Sipil, 2024)
Sugio Village Market is a traditional market located in Sugio Hamlet, this market is the only market in Sugio sub-district therefore this market is always crowded with people who want to shop for basic necessities every day. Market activity that causes an increase in the volume of vehicles entering and leaving the sugio market at certain hours makes it difficult for some vehicles to find a place to park. The method used in this study is a field survey by recording vehicle license plates in and out of the parking area. From the vehicle data is then analyzed to obtain accumulation, duration, parking volume, parking turnover rate, parking index and parking space needs. The results of this research were that the highest parking accumulation for motorbikes was 29 vehicles, while the highest accumulation for cars was 9 vehicles, the highest parking volume for motorbikes was 118 vehicles and the highest parking volume for cars was 12 vehicles, the highest average parking duration for bicycles. motorbikes are 1.91 hours/vehicle while for cars it is 3.5 hours/vehicle, the maximum parking capacity which can accommodate motorbikes is 204 vehicles/hour and to accommodate cars is 3 vehicles/hour, the highest parking index for motorbikes of 1.56 and the highest parking index for cars is 3.5, the highest parking turnover rate for motorbikes is 0.549 vehicles/srp/hour and the highest parking turnover rate for cars is 0.400 vehicles/srp/hour, for parking space needs additional area is needed land of 31.5 m2 for parking on the east side and 19.85 m2 for parking for motorbikes on the south side, while for cars an additional parking area of 113.75 m2 is needed in the area on the south side.